A Flexible System for Cultivation of Methanococcus and Other Formate-Utilizing Methanogens. (19th November 2017) - Long, Feng; Wang, Liangliang; Lupa, Boguslaw; Whitman, William B.
Abstract : Many hydrogenotrophic methanogens use either H2 or formate as the major electron donor to reduce CO2 for methane production. The conventional cultivation of these organisms uses H2 and CO2 as the substrate with frequent replenishment of gas during growth. H2 is explosive and requires an expensive gassing system to handle safely. Formate is as an ideal alternative substrate from the standpoints of both economy and safety but leads to large changes in the culture pH during growth. Here, we report that glycylglycine is an inexpensive and nontoxic buffer suitable for growth of Methanococcus maripaludis and Methanothermococcus okinawensis . This cultivation system is suitable for growth on liquid as well as solid medium in serum bottles. Moreover, it allows cultivation of liter scale cultures without expensive fermentation equipment. This formate cultivation system provides an inexpensive and flexible alternative for the growth of formate-utilizing, hydrogenotrophic methanogens.